Effect of Different Concentrations of Triple Antibiotic Paste Used in Root Canal Disinfection on the In Vitro Formation of Enterococcus faecalis Biofilms - Pineda-Vélez, Eliana (2026)
Enterococcus faecalis biofilms are a major cause of persistent endodontic infection and treatment failure. Triple antibiotic paste (TAP) is widely used, yet the optimal concentration that maximizes antibiofilm efficacy while minimizing cytotoxicity remains uncertain. This study aims to determine the minimum inhibitory concentration (MIC) of a modified TAP (ciprofloxacin–metronidazole–amoxicillin) against E. faecalis and to evaluate the effect of clinical and subinhibitory (sub-MIC) concentrations on in vitro biofilm formation. E. faecalis was cultured in brain heart infusion. MIC was determined by broth microdilution with resazurin as a viability indicator. Biofilm assays were performed in 96-well plates preconditioned for antibiotic adsorption. Standardized inocula were incubated 48 h (with medium renewal at 24 h). Biofilms were detached by sonication, serially diluted, drop-plated on BHI agar, and enumerated as CFU/mL. Percentage biofilm reduction was calculated relative to growth controls. Experiments were run in triplicate. The MIC of TAP against planktonic E. faecalis was 0.038 µg/mL. All concentrations tested reduced biofilm formation significantly versus MIC. Sub-MIC levels of 0.076 and 3.0 µg/mL produced similar reductions (p > 0.05). Higher sub-MIC concentrations—6.1, 24, and 49 µg/mL—achieved reductions approaching 100%, comparable to the clinical concentrations of 1000 and 2500 µg/mL (p > 0.05). Findings reveal a dose-dependent antibiofilm effect and highlight that some sub-MIC exposures can outperform the MIC for biofilm control. TAP exhibits a dose-dependent antibiofilm effect against E. faecalis, and concentrations below those commonly used clinically can markedly suppress biofilm formation in vitro. Sub-MIC levels equivalent to 1/1280, 1/640, and 1/160 of the MIC showed outstanding efficacy, suggesting the potential for lower-dose TAP protocols that preserve antibacterial activity while reducing adverse effects and antimicrobial resistance risk. Further studies must validate sub-MIC TAP regimens in multispecies biofilms and clinical settings.